2006
DOI: 10.1097/01.brs.0000228716.60863.ab
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Wear Assessment of the Charit?? Artificial Disc According to ASTM Recommendations

Abstract: Under these test conditions, the Charité Artificial Disc produced minimal wear debris. Debris size and morphology tended to be similar to other CoCr-UHMWPE joints. More testing is necessary to evaluate the implants under a spectrum of loading conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…The results of these tests have been similar to those observed in other metal-polyethylene articulating devices, with wear rates being within the 2-20 mm 3 /MC range [14][15][16][17]. Although comparisons to other implants are useful, further research needs to be undertaken in order to understand the wear processes within TDR, the tribological conditions that will be specific to TDR and the effect of wear debris upon local spinal tissues, particularly with reference to macrophage activation and osteolysis.…”
Section: Introductionsupporting
confidence: 73%
“…The results of these tests have been similar to those observed in other metal-polyethylene articulating devices, with wear rates being within the 2-20 mm 3 /MC range [14][15][16][17]. Although comparisons to other implants are useful, further research needs to be undertaken in order to understand the wear processes within TDR, the tribological conditions that will be specific to TDR and the effect of wear debris upon local spinal tissues, particularly with reference to macrophage activation and osteolysis.…”
Section: Introductionsupporting
confidence: 73%
“…Therefore, the functional biological activity values in our study 56 are analogous to, but not directly comparable with, the results reported by Fisher's group 46 . Studies other than our own 6,57 focusing on the characteristics of polyethylene particles in the lumbar spine are, for the most part, limited to an in vitro study by Serhan et al 58 . In their study, particle sizes visualized with an environmental scanning electron microscope ranged from submicrometer to >10 mm; however, the mean particle size (5 mm) was an order of magnitude larger than the mean particle size (0.72 mm) in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Initial experimental studies conducted under designer/manufacturer auspices reported that the design had negligible wear propensity [12,23]. Another experimental study, by Nechtow et al [16], showed that the Charité could have either very little wear, or significant wear, depending on the input parameters used.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory simulator tests and, more recently, computational wear simulations, have therefore been increasingly used to predict the long-term wear behavior of TDRs [5,21,23]. Consensus standards and a guidance document for wear testing of TDRs have been developed by the ISO (18192-1) and ASTM (F2423-05), respectively.…”
Section: Introductionmentioning
confidence: 99%